The OBJECTIONS Of IMAM IBN RAJAB Al-HANBALI On The SCHOLAR THROUGH His BOO; (FATH Al-BARI SHARH SAHIH BUKHARI)-A MODREN STUDY ( OBJECTIONS Because Of TALK In The NARRATOR) (Islamic Sciences Journal, 2023)
The science of Ashraf after the Quran is the talk of the Messenger of Allah - peace be upon him- , And the greatest closeness to God after his book, is to draw close to the servant of the year of the Prophet, May God have come from this nation of men of science, God save them Sunnah, and these scholars Imam Ibn Rajab, who is one of the senior imams of the eighth century in the graduation and explanation and clarification He was one of the most distinguished, and was one of the imams who gathered between the jurisprudence and the Hadith, and Imam Ibn Rajab was acceptable in most of his rulings Imams critics, and this research entitled objections of Imam Ibn Rajab because of talk in the narrator, where the researcher studied ten objections, according to the origins of scientific research.
Keywords: Ibn Rajab, hadith, aietirad , natija , alrawi.